A Groundwater Modelling Investigation of Greywater Disposal : South Tarawa, Kiribati - Jazayeri, Amir (World Bank, Washington, DC, 2019)
This report focused on a numerical modelling assessment of the possible effects of greywater reuse on the freshwater lenses in South Tarawa, Kiribati. Conceptual models and 2D cross-sectional numerical models of selected transects of Betio, Bairiki and Bikenibeu Islands were developed based on available field data. Simulations then were used to assess greywater transport and its effects on freshwater lenses in current situation and future scenarios. The modelling results show that adding the greywater discharge increases notably the freshwater thickness compared to the baseline scenario where greywater discharge is neglected. Eight scenarios were simulated to test the influence of rainfall dynamics and groundwater abstraction rates on the contribution of greywater disposal on freshwater lens thickness. The report then provides recommendations for future work to enhance the outcomes of future modelling efforts and the feasibility of indirect greywater reuse.